2012
DOI: 10.1242/bio.20123392
|View full text |Cite
|
Sign up to set email alerts
|

Myomegalin is necessary for the formation of centrosomal and Golgi-derived microtubules

Abstract: SummaryThe generation of cellular microtubules is initiated at specific sites such as the centrosome and the Golgi apparatus that contain nucleation complexes rich in γ-tubulin. The microtubule growing plus-ends are stabilized by plus-end tracking proteins (+TIPs), mainly EB1 and associated proteins. Myomegalin was identified as a centrosome/Golgi protein associated with cyclic nucleotide phosphodiesterase. We show here that Myomegalin exists as several isoforms. We characterize two of them. One isoform, CM-MM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
86
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(90 citation statements)
references
References 55 publications
4
86
0
Order By: Relevance
“…Pericentrin, AKAP9, CDK5RAP2 and myomegalin have been implicated in γTuRC recruitment to the centrosome (Fong et al, 2008;Takahashi et al, 2002;Zimmerman et al, 2004) and to the Golgi, which functions as a non-centrosomal MTOC (Rivero et al, 2009;Roubin et al, 2013;Wang et al, 2010). All of these proteins contain a CM1 motif (Lin et al, 2014(Lin et al, , 2015Samejima et al, 2008;Sawin et al, 2004), whereas an SPM motif is found only in pericentrin and AKAP9 (Lin et al, 2014(Lin et al, , 2015.…”
Section: Introductionmentioning
confidence: 99%
“…Pericentrin, AKAP9, CDK5RAP2 and myomegalin have been implicated in γTuRC recruitment to the centrosome (Fong et al, 2008;Takahashi et al, 2002;Zimmerman et al, 2004) and to the Golgi, which functions as a non-centrosomal MTOC (Rivero et al, 2009;Roubin et al, 2013;Wang et al, 2010). All of these proteins contain a CM1 motif (Lin et al, 2014(Lin et al, , 2015Samejima et al, 2008;Sawin et al, 2004), whereas an SPM motif is found only in pericentrin and AKAP9 (Lin et al, 2014(Lin et al, , 2015.…”
Section: Introductionmentioning
confidence: 99%
“…Apparently, Pde4dip functions as an anchor to localize components of the cAMP-dependent pathway to the Golgi apparatus/centrosomal region of the cell. Pde4dip has also been described as a microtubule nucleation activator and is related to regulating microtubule growth (11). Depletion of Pde4dip delays microtubule growth from the centrosome and Golgi apparatus.…”
Section: Discussionmentioning
confidence: 99%
“…Pde4dip is also called myomegalin and interacts with the cyclic nucleotide phosphodiesterase 4D. It is thought to function as a microtubule nucleation activator (11) and as an anchoring protein that sequesters members of the cyclic AMP (cAMP)-dependent pathway to the Golgi apparatus and to centrosomes (12).…”
Section: Importancementioning
confidence: 99%
“…Four genes encode over 20 isoforms of this protein, and they are involved in intracellular signaling [57]. Intracellular signaling and cross-talk occurs between cells and between pathways, and between tissues.…”
Section: Secondary Responsementioning
confidence: 99%
“…Pathway interactions operate in multiple directions. The cAMP phosphodiesterases are required for cell signaling and crosstalk [57]. Certain isoforms of myomegalin are necessary for centrosomal microtubule formation [58] and protein trafficking between Golgi and endoplasmic reticulum [59].…”
Section: Secondary Responsementioning
confidence: 99%